2022
DOI: 10.3390/ijerph19063372
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences between Medical Students in the Assessment of the Fear of COVID-19

Abstract: Background: Differing expressions of the fear of COVID-19 between men and women can potentially increase both immediate and long-term physical health risks. We predicted that women students would express greater fear of COVID-19. Methods: We used an Internet-delivered Fear of COVID-19 Scale (FCV-19S) to assess fear among men (n = 100) and women (n = 272) from a larger population of academic medical center members (n = 1761). Sex differences in emotional and physical symptoms were assessed as subcategories with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, long-term living in a limited space can cause people to feel anxious [3]. Qiu et al [4] and Trapp et al [5] found that people are more prone to anxiety during travel restrictions. Specifically, women are more prone to anxiety than men, and people aged 18 to 30 and over 60 are more prone to anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term living in a limited space can cause people to feel anxious [3]. Qiu et al [4] and Trapp et al [5] found that people are more prone to anxiety during travel restrictions. Specifically, women are more prone to anxiety than men, and people aged 18 to 30 and over 60 are more prone to anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Consistency testing: the calculation results are checked according to the consistency relation (C.R. ), as shown in Equation (5).…”
mentioning
confidence: 99%